FAIR Video Case Study: Stephen Livingstone - Automated mapping of Antarctic surface meltwater (dataset and code) - Sort Of. Films; Stephen Livingstone; Peter Tuckett; Jenni Adams (2022)
A video case study in which Dr Stephen Livingstone discusses the application of FAIR data and software principles to a research project on the automated mapping of Antarctic surface meltwater, led by one of Dr Livingstone's PhD students, Peter Tuckett. FAIR refers to the principles applied to make research data and software findable, accessible, interoperable and reusable. Filmed and produced by Sort Of. Films in May-July 2022. Interview conducted by Jenni Adams (University of Sheffield Library) The file UoS_FAIR_Stephen_Livingstone_FINALCUTmp4 contains the video itself, while the file UoS_FAIR_Stephen_Livingstone_FINALCUTmp4.mp4.srt contains the subtitles.